Duration and temporal dispersion measurements in CIDP subjects from the Polyneuropathy And Treatment with Hizentra (PATH) study - Menon, Deepak; Vijayan, Joy; Lawo, John-Philip; Mielke, Orell; Ngo, Mylan; Dela Cruz, James; Bril, Vera (RRNMF Neuromuscular Journal, 2021)
Abstract: Introduction: Distal compound muscle action potential (dCMAP) duration and temporal dispersion (TD) are electrophysiological hallmarks of demyelination and important for the diagnosis of CIDP. While the impact of CIDP treatment on other nerve conduction parameters has been examined, the effects on dCMAP and TD remain unexplored. The aim of the study was to examine the impact of withdrawal of immunoglobulin treatment on dCMAP duration and TD, and also the influence of the measurement technique on dCMAP duration and TD. Methods: Nerve conduction studies were analyzed from the PATH (Polyneuropathy And Treatment with Hizentra) study which randomized patients with CIDP to two doses of IgPro 20 and placebo. Distal CMAP duration and TD were obtained by two methods of measurements (D1 and D2, TD1 and TD2) from the median and peroneal nerves. Results: The dCMAP and TD were obtained from 389 tracings. While the two methods of measurement showed differences in D1 and D2 with D2 longer than D1 in all the three groups, there was no difference between the TD1 and TD2. There was no difference at baseline in dCMAP duration or TD among the three groups. At the end of treatment, patients in the placebo arm had no worsening of dCMAP and TD compared to baseline or the treated groups. Conclusion: dCMAP duration and TD did not show a difference between treated and placebo groups, and may be less sensitive measures than other nerve conduction parameters when evaluating changes in treatment. The method of dCMAP duration measurement does not affect TD as long as a consistent method is followed.